Formação continuada de técnicos administrativos em educação: um estudo sobre sua (des)articulação com a política nacional de desenvolvimento de pessoas - Freire Junior, José de Miranda (2022)
The present study analyzed the national policy of people development and continuing education of Administrative Technicians in Education (TAEs) and how this is (dis)articulated from the personnel training policy developed by PROGEP/UFPB, in the early years of implementation of the new National Policy of People Development (PNDP). The theoretical studies began with reference to the State Reform, the model of managerial administration and Public Administration, advancing to the policy of investing in the knowledge of individuals in Public Administration, with attention to the National School of Public Administration (ENAP) and its insertion in the public administration scope of the public servant training policy, concluding with the training policy for administrative technicians in education. In methodological terms, the research carried out was qualitative, descriptive, explanatory and exploratory, being developed through a bibliographic study and legal documents, with interviews with two managers from PROGEP/UFPB and one manager from ENAP. The generated data were treated and analyzed from the content analysis of Bardin (2009). The studies showed that the central body of the federal public administration the Secretariat for Personnel Management and Performance of the Ministry of Economy, through ENAP, in the new PNDP, gains greater control over the training process of federal servants, becoming responsible for identify, follow up, monitor and direct, through SIPEC, the way in which public agencies of the federal executive will invest their resources in personnel training. At UFPB, with the new PNDP, managers, in dialogue with civil servants, began to fill in their demands for training and qualification directly in SIPEC. The central role that ENAP assumes in the new policy was highlighted, as an instance of training servers, leaving the HEIs to offer courses that are not included in their platform. Despite this centrality being pointed out as a strategy to seek greater efficiency in the application of resources, it represents greater control over the training processes previously developed at the initiative of the universities, leaving the Pro-Rectory only to offer courses of a supplementary nature. The study concludes with reference to the advances and to what there is to invest in the University within the scope of the new PNDP, highlighting the investment in studies and discussions of this policy at the UFPB, since it was implemented in a pandemic period, without due debate and discussion. The importance of investing in the development of people, including the TAEs, is highlighted, in line with the new directions that are intended to be given to the university, to enforce its social function, through the transfer of knowledge, following the principle of inseparability between teaching, research and extension.